Legal and Regulatory Framework of European Energy Markets: Competition Law and Sector-Specific Regulations - Burkhalter, Cansu D. (Tectum Verlag, 2020)
Since the beginning of the 1990s, Europe has been struggling to establish a competitive as well as a fully integrated internal energy market. Until the early 1990s, the European energy markets consisted of national monopolies possessing vertically integrated structures. They were also still nationally segregated. Since, the EU has made the decision to open European energy markets to competition and subsequently establish an internal energy market.The European energy markets are currently controlled by a dual structure consisting of two different regulatory frameworks: competition law and sector-specific regulations. The primary goal of these legal instruments is the establishment of an internal energy market.This book aims at analysing the development of the European energy markets and policies from the perspective of competition law as well as sector-specific regulations and, hence, identifying the problems regarding the introduction of competition into the energy markets.